Effectiveness of Problem Based Learning Model of Learning About The Fiqh Class VIII Learning in Middle School Al-Firdaus Karangploso Malang - Moh. Mukhlas; Muazzam Muazzari Al Muhtadi Billah Muazzari Al Muhtadi Billah (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
Learning outcomes are changes in one's behaviour that include cognitive, affective, and psychomotor abilities after following a particular teaching learning process. Education and teaching are said to be successful if the students visible changes are the result of the teaching learning process which is the process that is taken through programs and activities designed and implemented by the teacher in the teaching process. Therefore, a teacher must have innovations in teaching one of them using the method of learning Problem based learning. The results of the study taken from the semester exam on the Fiqh teaching eyes in SMP Plus Al-Firdaus Karangploso Malang, is quite satisfactory.In this study aims: (1) to know the results of students learning after the application of learning methods of Problem based learning on the subjects of Fiqh class VIII SMP Plus Al-Firdaus Karangploso Malang. (2) to explain the influence of the implementation of methods of learning Problem based learning on learning outcomes Fiqh class VIII of SMP Plus Al-Firdaus Karangploso Malang. The research was designed with experiments using the experimental design quasi-One Group Pretest Posttest Design which aims to determine the difference in learning outcomes before application of learning model and after application of learning model of problem based learning and also to know the presence or absence of learning method of problem based learning to improve learning outcomes. The instrument of data collection using tests and data analysis using test normality, test homogenity, Test T. The results of this study showed that: (1) based on data analysis obtained pretests value with an average of 43.28 and posstest value with an average of 85.52. (2) There are influences of the implementation of the Problem based learning method on the learning results of the Fiqh study based on statistical analysis by using the test obtained the result of 0.000 < 0.05.